Structural Characteristics and Deformation Evolution of an Intra-Continental Fold-Thrust Belt in Eastern Sichuan: Insights Into Analogue Sandbox Models - Wang, Yang-Shuang; Xu, Mo; Yang, Yan-Na; Xia, Qiang; Jiang, Bing; Yang, Chang; Zhang, Heng (Frontiers in Earth Science, 2022)
The east Sichuan area is a typical fold-and-impulse zone, bounded by the Qiyue Mountain Fault, with septal folds on the east and septal folds on the west. Based on the previous geological mapping and surface geological structure research, this study is based on the fault-related folding theory, and the tectonophysical simulation experiments are conducted to investigate the tectonic geometry and kinematics of the Eastern Sichuan fold-impulsive zone. The experiments were conducted by selecting different experimental materials, changing the physical properties of the cover, the friction between the cover and the basement, the number of slip layers and the burial depth, and other factors, and finally presenting the similarity with the real The morphological characteristics similar to the real geological structure were finally presented. The results show that the deformation style is influenced to some extent by the brittle shear strength and the basement ductile shear strength, and the different interlayer cohesion between the competent and incompetent layers and the high rheology and burial depth of the slickensides play a crucial role in the formation of the final evolution of the Eastern Sichuan fold fault zone. The step-like system composed of the lower crustal crystalline basement detachment surface, regional boundary fractures and the overlying Cambrian and Triassic synclines is a necessary condition for the formation of the Eastern Sichuan Fold and Fault Zone and controls the overall evolution of the zone. Under the action of multiple phases of tectonic activity with different orientations of main stresses, the geological phenomenon of multiple phases of folding in different directions superimposed on each other in the present-day eastern Sichuan area was formed. The developed karst is not conducive to the construction of the project tunnel in the area where tightly closed the back-slope and fissure and normal fault developed in the Eastern Sichuan Fold and Fault Zone.